2020
DOI: 10.1016/j.tifs.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

anti-HCoV: A web resource to collect natural compounds against human coronaviruses

Abstract: Background . A novel coronavirus, the SARS-CoV2, was revealed to be the cause of COVID19, the pandemic disease that already provoked more than 555.324 deaths in the world (July 10, 2020). No vaccine treatment has been defined against SARS-CoV2 or other human coronaviruses (HCoVs), including those causing epidemic infections, neither appropriate strategies for prevention and care are yet officially suggested. Scope and approach . We reviewed sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 94 publications
(143 reference statements)
0
3
0
Order By: Relevance
“…Therewith, the pharmaceutical industry and scientific research are focusing on exploration of natural products particularly, MAPs producing several bioactive molecules approved effective against viral infections, including those from coronaviruses, enterovirus, hepatitis B, hepatitis C, herpes simplex virus (HSV), human immunodeficiency (HIV), and influenza viruses (IFV) (Monticolo et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therewith, the pharmaceutical industry and scientific research are focusing on exploration of natural products particularly, MAPs producing several bioactive molecules approved effective against viral infections, including those from coronaviruses, enterovirus, hepatitis B, hepatitis C, herpes simplex virus (HSV), human immunodeficiency (HIV), and influenza viruses (IFV) (Monticolo et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“… 10 However, the catalytic domains of the proteins responsible for RNA synthesis and replication are highly conserved ( Figure 1 ). 11 , 12 These proteins present attractive targets for the identification of drugs active across the entire genus Betacoronavirus . The application of computer-aided drug design tools allows for the inexpensive and rapid evaluation of NP structures in published databases and the scientific literature for in silico screening.…”
Section: Broad-spectrum Potential For the Genus Betacoronavirusmentioning
confidence: 99%
“…A healthy eating pattern is mainly based on foods that have balanced amounts of good quality nutrients (vegetables, fiber-rich legumes, fruits and whole grains), and on limited amounts of red and processed meats, sugarsweetened beverages, highly processed foods and refined grain products [2]. In addition, specific bioactive compounds, such as sterols, indoles and phenols, naturally present in many foods, mainly in vegetables and fruits, are known to enrich food quality [12], acting as protective, preventing and caring agents in inflammation [13,14], disease [15,16], infections [17,18] and in chronic diseases such as cancer [19,20]. Indeed, it has been shown that improved diet quality reduces the risk of cancer deaths from 11% to 23% [21].…”
Section: Introductionmentioning
confidence: 99%